The effect of peroral administration of toxic cyanobacteria on laboratory rats (Rattus norvegicus var. alba) - Adamovsky, Ondrej; Kopp, Radovan; Zikova, Andrea; Blaha, Ludek; Kohoutek, Jiri; Ondrackova, Petra; Paskerova, Hana; Mares, Jan; Palikova, Miloslava (Neuro endocrinology letters, 2011)
OBJECTIVES: The toxic cyanobacteria are a serious problem for water supply systems, recreation, and agriculture. Cyanobacteria produce numerous bioactive compounds including microcystins - the most studied cyanobacterial hepatotoxins. Only rare studies addressed realistic situation, i.e. impact of MCs accumulated in the fish tissues on the overall physiology. The aim of the present study was to provide a model simulation of the simple food chain for evaluation of impacts of cyanobacteria on the rat physiology under different exposure scenario. METHODS: Experimental rats were fed with food with fish meat, which contained external additions of isolated microcystins as well as toxic cyanobacteria Microcystis, nontoxic cyanobacteria Arthrospira and green alga Chlorella. Subgroups of the animals were also challenged with a model antigen KLH to investigated immune-related parameters. We studied parameters of oxidative stress in the liver as levels of lipid peroxidation and glutathion levels. Series of hematological, biochemical and immunological parameters were also investigated. RESULTS: Although considerable amounts of microcystins were administered to rats, all levels of MCs were under the detection limit (1 ng/g fresh weight) in the rat tissues using tandem LC/MS. Only some conjugates of microcystins with cystein and glutathion were detected in the rat liver exposed to Microcystis biomass (values were around the detection limit). Statistically significant depletion of body and liver weight was observed in groups with microcystin addition in comparison with all other groups. Rats exposed to MCs had stimulated immune system (showed higher antibody answer on administered antigen). Also modulation of some lymphocyte subpopulations was recorded with the most interesting observation of stimulated NK cell numbers in groups exposed to isolated toxins (but not to biomass containing the same toxin amount). CONCLUSIONS: Our study demonstrates that oral exposure to microcystins in the diet may induce some detoxification responses and modulation of some hematological and immunological parameters.
Keywords: Animals, Laboratory; přijímání potravy; Cyanobacteria Toxins; Eating; mikrocystiny; peroxidace lipidů; rybí výrobky; krysa rodu Rattus; Administration, Oral; zvířata; mořské toxiny; Marine Toxins; Glutathione; potkani Wistar; sinice; laboratorní zvířata; Rats, Wistar; Male; kontaminace potravin; Bacterial Toxins; Food Contamination; glutathion; Fish Products; Rats; Animals; aplikace orální; bakteriální toxiny; Cyanobacteria; mužské pohlaví; Microcystins; Lipid Peroxidation; toxiny kmene Cyanobacteria